2021
DOI: 10.4102/phcfm.v13i1.2873
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of primary healthcare workers regarding the prevention and control of non-communicable diseases in Osun State, Nigeria: A rural-urban comparison

Abstract: Background: There is a rising burden of non-communicable diseases (NCDs) in the sub-Saharan Africa, and calls for integration of management of selected NCDs with primary healthcare (PHC) have been unrelenting. Cost-effective interventions for the prevention and control of NCDs can be delivered at PHC facilities in low-resource settings by clinical healthcare workers (HCWs).Aim: This study compared the knowledge of HCWs in PHC facilities regarding the prevention and control of NCDs in rural and urban local gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…Overall, 29.9% (95% CI: 23.6-36.2%) of HEWs had a low level of NCD knowledge, 32.6% (95% CI: 26.2-39.0%) of HEWs had a moderate level of NCD knowledge, and 37.5% (95% CI: 30.8-44.2%) of HEWs had a high level of NCD knowledge. In contrast, a Nigerian study found that 23.0% of primary healthcare workers had adequate NCD knowledge [40], significantly lower than our findings. This variation could be due to knowledge score dimensions and classification differences.…”
Section: Discussioncontrasting
confidence: 99%
“…Overall, 29.9% (95% CI: 23.6-36.2%) of HEWs had a low level of NCD knowledge, 32.6% (95% CI: 26.2-39.0%) of HEWs had a moderate level of NCD knowledge, and 37.5% (95% CI: 30.8-44.2%) of HEWs had a high level of NCD knowledge. In contrast, a Nigerian study found that 23.0% of primary healthcare workers had adequate NCD knowledge [40], significantly lower than our findings. This variation could be due to knowledge score dimensions and classification differences.…”
Section: Discussioncontrasting
confidence: 99%
“…Due to the chronic nature of NCDs, people living with these diseases and their risk factors require sustained person-centred and community-based care [13]. This would ideally be achieved through the PHC health system.…”
Section: Introductionmentioning
confidence: 99%
“…Access to quality and essential NCD interventions is further compounded by inadequate and maldistribution of skilled health workers, particularly physicians and nurses [13]. Consequently, NCD care at the PHC level is mainly handled by community health workers (CHWs), whose training and skills are generally considered insufficient for NCD management and prevention [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have a major effect when supporting patients with self-management of their condition particularly using the proactive care management model and decision making support approaches [18][19][20][21][22]. Numerous studies outside SSA [16, [23][24][25][26][27] and within Africa [28][29][30][31][32][33][34][35] report low knowledge levels of diabetes and diabetes care among nurses. However, the factors that hinder and promote the nurses' acquisition of diabetes knowledge are not well established.…”
Section: Introductionmentioning
confidence: 99%